Salivary oxytocin in autistic patients and in patients with intellectual disability - Pichugina, Yulia A.; Maksimova, Irina V.; Berezovskaya, Marina A.; Afanaseva, Natalya A.; Pichugin, Aleksey B.; Dmitrenko, Diana V.; Timechko, Elena E.; Salmina, Alla B.; Lopatina, Olga L. (Frontiers in Psychiatry, 2022)
Background Assessing the role of oxytocin (OT) in the regulation of social interaction is a promising area that opens up new opportunities for studying the mechanisms of developing autism spectrum disorders (ASD). Aim To assess the correlation between the salivary OT level and age-related and psychopathological symptoms of children with intellectual disability (ID) and ASD. Methods We used the clinical and psychopathological method to assess the signs of ASD based on International Classification of Diseases (ICD-10), the severity of ASD was specified by the selected Russian type version “Childhood Autism Rating Scale” (CARS). Patients of both groups had an IQ score below 70 points. Results The median and interquartile range of salivary OT levels in patients with ID and ASD were 23.897 [14.260–59.643] pg/mL, and in the group ID without ASD - Me = 50.896 [33.502–83.774] pg/mL (p = 0.001). The severity of ASD on the CARS scale Me = 51.5 [40.75–56.0] score in the group ID with ASD, and in the group ID without ASD—at the level of Me = 32 [27.0–38.0] points (p < 0.001). According to the results of correlation-regression analysis in the main group, a direct correlation was established between salivary OT level and a high degree of severity of ASD Rho = 0.435 (p = 0.005). There was no correlation between the salivary OT level and intellectual development in the group ID with ASD, Rho = 0.013 (p = 0.941) and we have found a relationship between oxytocin and intellectual development in the group ID without ASD, Rho = 0.297 (p = 0.005). There was no correlation between salivary OT and age, ASD and age. Conclusion The results of this study indicate that patients in the group ID with ASD demonstrated a lower level of salivary OT concentration and a direct relationship between the maximum values of this indicator and the severity of autistic disorders, in contrast to patients in the group ID without ASD.